Investigation of the Effect of Written and Visual Information on Anxiety Measured Before Magnetic Resonance Imaging: Which Method is Most Effective? - Yakar, Burkay; Pirincci, Edibe (Mdpi, 2020)
Background and objective: Magnetic resonance imaging (MRI) causes severe anxiety in some patients. Anxiety during MRI leads to prolongation of the procedure and deterioration of image quality, resulting in loss of labor and cost increase. The aim of this study was to investigate the effect of written and visual information on state anxiety in patients undergoing MRI. Material and Methods: A cross-sectional prospective study was conducted with 294 participants. The study was carried out between January 2019 and March 2019 at the Radiology Clinic of the tertiary university hospital. The participants were divided into 3 groups as group 1 (control group), group 2 (written information) and group 3 (visual information). The trait anxiety and state anxiety of the participants were measured by State-Trait Anxiety Inventory (STAI) inventory, which can measure both anxiety status. Results: There was no statistically significant difference between demographic characteristics and trait anxiety scores (p = 0.20) of all three groups. The state anxiety scores of group 3 were statistically lower than the group 2 (p < 0.001) and control group (p < 0.001). The state anxiety scores of group 2 were statistically lower than control group (p < 0.001). Conclusion: MRI anxiety can be reduced by visual and written information. Visual information may be more effective in reducing MRI anxiety than written information.
Keywords: magnetic resonance imaging; anxiety; information; STAI; MRI